Overexpression of the Mitotic Checkpoint Genes BUB1 and BUBR1 is Associated with Genomic Complexity in Clear Cell Kidney Carcinomas - Mafalda Pinto; Joana Vieira; Franclim R. Ribeiro; Maria J. Soares; Rui Henrique; Jorge Oliveira; Carmen Jerónimo; Manuel R. Teixeira (Cellular Oncology)
Background: A defective mitotic checkpoint has been proposed to contribute to chromosomal instability (CIN). We have previously shown that expression changes of the mitotic arrest deficiency (MAD) gene family plays a role in renal cell cancer (RCC) characterized by numerical chromosomal changes, namely papillary and chromophobe carcinomas, but nothing is known about the expression of mitotic checkpoint genes in the clear cell histotype (ccRCC).